Women's agency in nutrition in the association between women's empowerment in agriculture and food security: A case study from Uganda - Farzaneh Barak; Jackson Efitre; Robinson Odong, Hugo Melgar-Quiñonez (Wiley Periodicals LLC on behalf of Policy Studies Organization, 2023)
This study examined the relationship between women’s empowerment in agriculture (WEA), women’s agency in nutrition, and their food security. It aimed to quantify the moderating effect of women’s agency in nutrition on the association between WEA and food security. Data from the NutriFish project, a genderand nutrition-sensitive agricultural intervention in fishing villages in Uganda, were utilized. The study included 380 primary Ugandan female decision makers in dual adult households. WEA was measured using the Project-level Women’s Empowerment in Agriculture Index (pro-WEAI). Women’s agency in nutrition was assessed through measures of agency in regular diet, pregnancy diet, breastfeeding diet, and food purchase. Binary logit regression models were employed to estimate differential associations between WEA and food security, testing three-way interactions between WEA, agency in regular diet, and food purchase. Results showed that WEA was associated with a 0.18increase in the predicted probability of food security (p < .01). Women’s participation in food purchase decisions strengthened the WEA-food security association by 0.33 (p < .05). The results suggested that promoting women’s food purchase agency can enhance the positive link between WEA and food security. Prioritizing interventions empowering women in food purchase decisions improves food security in gender- and nutrition-sensitive programs.
Keywords: agency in nutrition; food purchase agency; food security; Uganda; women’s empowerment